Positive correlation between gene coexpression and positional clustering in the zebrafish genome - Zhang Louxin; Wu Wei; Ng Yen Kaow (BMC Genomics, 2009)
Abstract Background Co-expressing genes tend to cluster in eukaryotic genomes. This paper analyzes correlation between the proximity of eukaryotic genes and their transcriptional expression pattern in the zebrafish (Danio rerio) genome using available microarray data and gene annotation. Results The analyses show that neighbouring genes are significantly coexpressed in the zebrafish genome, and the coexpression level is influenced by the intergenic distance and transcription orientation. This fact is further supported by examining the coexpression level of genes within positional clusters in the neighbourhood model. There is a positive correlation between gene coexpression and positional clustering in the zebrafish genome. Conclusion The study provides another piece of evidence for the hypothesis that coexpressed genes do cluster in the eukaryotic genomes.